Motivations and their influence on loyalty in food festivals - Mauricio Carvache-Franco; Tahani Hassan; Orly Carvache-Franco; Lidija Bagarić; Wilmer Carvache-Franco (Cogent Arts & Humanities)
Food festivals are significant because they impact the growth of new businesses, the production of revenue for the government, the marketing of the tourist destination, and the development of the destination’s image. The present demand study is one of the first related to festivals in a Muslim population. The research aimed at (i) establishing the motivational dimensions of gastronomic festivals and (ii) determining the motivational dimensions that predict loyalty to gastronomic. The research was executed during the Bahrain Food Festival, which takes place in the state of Bahrain on the west coast of the Persian Gulf. Factor analysis was used to find the dimensions and the multiple regression model to identify the most important predictors of loyalty. The results demonstrate five motivational dimensions in gastronomic festivals: Local food, Socialization, Entertainment, Escape & novelty, and Art. The Escape and novelty factor was the most relevant predictor of loyalty, followed by entertainment. If we study festivals, we can collaborate with the development of destinations. The results, which are this research’s contribution to academic literature will help organizers develop management plans to benefit these events.